Flexibility and lability of a phenyl ligand in hetero-organometallic 3d metal–Sn(iv) compounds and their catalytic activity in Baeyer–Villiger oxidation of cyclohexanone. Issue 39 (22nd August 2017) - Hazra, Susanta; Martins, Nuno M. R.; Kuznetsov, Maxim L.; Guedes da Silva, M. Fátima C.; Pombeiro, Armando J. L.
Abstract : An intermetallic Ph-shift (Sn IV -to-Co III ) leads to a Co III (Ph)–Sn IV (Ph) and a mononuclear Co III (Ph) compounds, while a M⋯π(Ph) interaction in the Ni II /Cu II –Sn IV systems represents an intermediate stage of that Ph-shift. Abstract : The single compartmental Schiff base N, N ′-ethylenebis(salicylaldimine) (H2 L) and [SnPh2 Cl2 ] were utilized to synthesize heterobimetallic 3d metal–Sn complexes, the Co III Sn IV compound [SnPhCl2 (1κ O 2 N 2, 2κ O 2 -μ-L)(μ-OMe)CoPh] (1 ), the Ni II Sn IV compound [SnPh2 Cl2 (1κ O 2 N 2, 2κ O 2 -μ-L)Ni] (2 ) and the Cu II Sn IV compound [SnPh2 Cl2 (1κ O 2 N 2, 2κ O 2 -μ-L)Cu] (3 ). Attempting to prepare the ethoxido bridged compound analogous to1 (in ethanol) gives the phenylcobalt(iii ) complex [Co(κ O 2 N 2 )Ph(H2 O)] (1A ). Single crystal X-ray structure analyses reveal that1 is derived from an intermetallic (Sn to Co) phenyl shift and that1A is a transmetallated product; in compounds2 and3, the phenyl groups remain coordinated to Sn IV but one of the π rings interacts with the 3d-metal. Thus, while systems1 and1A show the lability of the phenyl ligand, 2 and3 reveal its flexible nature. Theoretical DFT calculations demonstrate that the conceivable Ph group shift occurs in the oxidized Co III intermediate [Sn IV Ph2 Cl2 (κ O 2 N 2 -μ-L)Co III (MeO)] (5 ) rather than in the corresponding Co II species [Sn IV Ph2 Cl2 (κ O 2 N 2 -μ-L)Co II (MeOH)] (4 ). Their catalytic studies in the Baeyer–Villiger oxidation of cyclohexanone into ε-caprolactone with two different oxidants reveal that the sacrificial aldehyde method (with dioxygen/benzaldehyde) is better than that with aqueous H2 O2 (30%). The effects of various reaction parameters such as solvent, catalyst amount, temperature, time and heating method were studied allowing the achievement of yields up to 83% with 89% selectivity.